IN VITRO EVALUATION OF ANTIOXIDANT POTENTIAL OF ETHANOLIC EXTRACT OF PHYLLANTHUS AMARUS- A MAGICAL HERB - NEELU SINHA; SANGEETA SHUKLA (International Journal of Pharma and Bio Sciences, 2015)
For use of herbal medicines all over the globe, it is important to evaluate antioxidant activity. Antioxidant activity of ethanolic extract of Phyllanthus amarus were evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity and hydrogen peroxide scavenging activity. The results of present study showed potent antioxidant activity of ethanolic extract of plant extract.